2023
DOI: 10.3390/ijms24119285
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of the Immunotherapeutic Drug Anti-Programmed Death 1 with Lenalidomide Enhances Specific T Cell Immune Responses against Acute Myeloid Leukemia Cells

Abstract: Immune checkpoint inhibitors can block inhibitory molecules on the surface of T cells, switching them from an exhausted to an active state. One of these inhibitory immune checkpoints, programmed cell death protein 1 (PD-1) is expressed on T cell subpopulations in acute myeloid leukemia (AML). PD-1 expression has been shown to increase with AML progression following allo-haematopoeitic stem cell transplantation, and therapy with hypomethylating agents. We have previously shown that anti-PD-1 can enhance the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Greiner et al showed that CD4 + and CD8 + T cells from AML patients could respond to peptides from the mutated regions of NPM1 [43]. They found that AML NPM1 mut patients with CTL responses against NPM1 mut peptide had better overall survival [45] and used LAAs as a specific method of stimulating T-cell immune responses against LSCs and determining which combinations of immunotherapeutics could further enhance AML cell killing [82].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greiner et al showed that CD4 + and CD8 + T cells from AML patients could respond to peptides from the mutated regions of NPM1 [43]. They found that AML NPM1 mut patients with CTL responses against NPM1 mut peptide had better overall survival [45] and used LAAs as a specific method of stimulating T-cell immune responses against LSCs and determining which combinations of immunotherapeutics could further enhance AML cell killing [82].…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of immunotherapeutic approaches are believed to increase antigenspecific immune responses against leukemic cells including LPC/LSCs. In this study, we used a combination of LAA-peptides with the ICI, αPD-1 (nivolumab), and lenalidomide to enhance the killing of LSC/LPCs ex vivo [82]. We used primary cells from AML patients and observed the T-cell responses of all patients in vitro.…”
Section: The Immune Checkpoint Inhibitors -αPd-1 and αPd-l1mentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of next generation immunotherapeutic strategies including Boolean gating, reversing T cell exhaustion, and split/SUPRA CARs (recently reviewed in [115]), we see an opportunity to address the current challenges limiting the safety and efficacy of CAR-T cells for cancer treatment. It is likely that a combinational approach can provide a safe delivery method for immunotherapeutic targeting of AML, and, indeed, recent studies suggest the combination of an immune checkpoint inhibitor and antigen targeting, as well as immune modulation, could further enhance anti-leukaemic responses [116,117].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent in vitro study on leukemic cells and lenalidomide in combination with nivolumab (anti-PD-1), suggested that certain populations of cells might benefit more from ICI use. That combination was shown to be highly effective in supporting a population of leukemic antigen-specific cytotoxic T cells, especially toward blasts of the NPM mut AML group [ 11 ]. In contrast, blockage of PD-L1 on leukemic cells was associated with cell cycle arrest, inhibition of proliferation and activation of apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%